A comprehensive review of navigating urbanization induced climate change complexities for sustainable groundwater resources management in the Indian subcontinent - Zullyadini A. Rahaman (Tanjung Malim, 2024)
A comprehensive review of navigating urbanization induced climate change complexities for sustainable groundwater resources management in the Indian subcontinent by Zullyadini A. Rahaman